2022
DOI: 10.3390/ijerph191811573
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence in Patients with Obstructive Pulmonary Diseases

Abstract: COPD is the third most common cause of death globally. Adherence rates in patients with obstructive pulmonary diseases usually range between 10% and 40%. The aim of the study was to evaluate the level of treatment adherence to inhaled therapy in patients with obstructive pulmonary diseases. A total of 325 patients, of mean age 63.04 ± 11.29, with COPD or asthma, were included into the study between 2020 and 2021. The following questionnaires were used: Beliefs about Medicines Questionnaire, Test of Adherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A previous study in Poland reported moderate level of adherence to medications among patients with COPD. 41 This research found that 74% of patients had sporadic noncompliance and concluded that patients with obstructive lung diseases have moderate medication adherence. 41 In addition, they found that the influence of beliefs about medicines on drug adherence is substantial.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study in Poland reported moderate level of adherence to medications among patients with COPD. 41 This research found that 74% of patients had sporadic noncompliance and concluded that patients with obstructive lung diseases have moderate medication adherence. 41 In addition, they found that the influence of beliefs about medicines on drug adherence is substantial.…”
Section: Discussionmentioning
confidence: 98%
“…The beliefs about continued inhaler use being harmful (better not to use daily, use as little as possible) are relevant to our questionnaire, in reference to the Horne model's "concerns about treatment" factor. These beliefs are included in factor 1 and are coincident with the BMQ's "Belief that medicines are harmful" factor, which is related to low adherence [24].…”
Section: Discussionmentioning
confidence: 99%
“…This perception of the need for treatment varies according to the intentionality of nonadherence: patients with intentional non-adherence had a lower perception of the need for their medication and a higher level of concerns about it due to adverse effects or habituation, among other aspects, compared to adherent patients [23]. Recent research confirms that the perceived need for inhaled medication is related to increased adherence, while the belief that these medications are harmful is a determinant of poor adherence [24].…”
Section: Introductionmentioning
confidence: 99%
“…Low adherence to treatment is an up-to-date challenge all around the world. Nearly half of patients with COPD have moderate and high compliance to long-term therapy and continuous exacerbation remission periods [ 20 ]. The remaining patients experience poor outcomes and reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%